Localization of environmental reflectors from a single measured transfer function - Zamaninezhad, Ladan; Annibale, Paolo; Rabenstein, Rudolf (6th International Symposium on Communications, Control and Signal Processing, ISCCSP 2014, 2014)
This paper introduces a method for localizing reflectors in one dominant direction of a three-dimensional acoustic enclosure. The method is based on the response of the acoustic environment to an acoustic excitation. Only a single sound source and a single microphone are required. A two-step algorithm is proposed. In the first step, the distance between the reflectors is determined from the estimation of resonant frequencies. In the second step, the distance of one of the reflectors from the sound source is determined by numerical optimization. An experiment in a real three-dimensional acoustic environment shows that the position of two reflectors at opposite walls can be localized with high accuracy using a single microphone. © 2014 IEE
Keywords: acoustic reflector localization; geometry estimation; Green's function; room acoustics